2022
DOI: 10.3847/1538-4357/ac55a1
|View full text |Cite
|
Sign up to set email alerts
|

Ages of Main-sequence Turnoff Stars from the GALAH Survey

Abstract: Main-sequence turnoff (MSTO) stars are good tracers of Galactic populations since their ages can be reliably estimated from atmospheric parameters. Based on the GALAH survey, we use the Yale rotation evolution code to determine the ages of 2926 MSTO stars with a mean age uncertainty of ∼10% considering the variation of C and O abundances. The ages of CO-poor stars are systematically affected by ∼10% due to the C and O abundances, globally shifting to ∼0.5 Gyr older compared to the results using solar metal mix… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 51 publications
(53 reference statements)
0
3
0
Order By: Relevance
“…Notably, at fixed [Fe/H], the abundance variations of individual elements exert a consequential impact on the overall metallicity Z, which subsequently determines the opacity of the stellar models. This, in turn, influences the efficiency of energy transfer and the thermal structure, thereby altering the evolution tracks on the H-R diagram and the main-sequence (MS) lifetime (e.g., VandenBerg et al 2012;Chen et al 2022). Consequently, in the context of stellar modeling, it is essential to consider the proper metal mixture in order to accurately characterize stars and determine their ages.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Notably, at fixed [Fe/H], the abundance variations of individual elements exert a consequential impact on the overall metallicity Z, which subsequently determines the opacity of the stellar models. This, in turn, influences the efficiency of energy transfer and the thermal structure, thereby altering the evolution tracks on the H-R diagram and the main-sequence (MS) lifetime (e.g., VandenBerg et al 2012;Chen et al 2022). Consequently, in the context of stellar modeling, it is essential to consider the proper metal mixture in order to accurately characterize stars and determine their ages.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Ge et al (2016) proposed the COextreme models, which treat oxygen abundance differently from the other α elements and add carbon abundance in the stellar evolution models. The models have been employed to determine the ages of thousands of metal-poor halo stars, disk stars, and MS turn-off stars (Ge et al 2016;Chen et al 2020Chen et al , 2022. These results showed that increasing oxygen abundance leads to smaller age determination for the stars with [Fe/H] < −0.2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation